TEACHER’S PERCEPTION TOWARDS THE IMPORTANCE OF EXTROVERSION IN IMPROVING EFL LEARNER’S INTERLANGUAGE - TAHRI AHLAM, ZOUAZA WALID (UNIVERSITY MOHAMED BOUDIAF - M’SILA, 2021)
Abstract Though extraversion is one of the most required personality traits in language learning and teaching area, it is still a relative aspect among EFL learners based on their learning styles . The present conduct investigates teachers‘ perspectives on the significance and importance of extraversion in improving EFL learner‘s interlanguage. To conduct this study, the qualitative approach was adopted. To support this approach,an interview was used to collect data. The analysis of data demonstrates that teachers have positive attitudes towards the importance of extraversion in second language learning. In addition to EFL learners‘ interlanguage improvement, extraversion helps them to develop critical thinking and autonomy. Moreover, the findings reveal that extraverts are easy to engage with and easily immerse themselves within second language context. The fulfillment of the study was hoped to collect teachers‘ teacher‘s views on the significance of extraversion and its effectiveness for a better second language learning improvement.
Keywords: Key words: extraversion, interlanguage teacher‘s views, second language learning and teaching, EFL learners